Fuzzy C-means clustering for DNA computing readout method implemented on LightCycler system - Saaid, M. F. M. (Society of Instrument And Control Engineers, 2008)
In the previous work, a readout approach for the Hamiltonian Path Problem (HPP) in DNA computing, based on the real-time polymerase chain reaction (PCR) was proposed. Based on this approach, real-time amplification was performed with TaqMan probes, and the TaqMan detection mechanism was exploited for the design and development of the readout approach. The readout approach consists of two steps: real-time amplification in vitro using TaqMan-based real-time PCR followed by information processing in silico to assess the results of real-time amplification, which in turn, enables extraction of the Hamiltonian path. However, the previous method used manual classification of two different output reactions of real-time PCR In this paper, the Fuzzy C-Means (FCM) clustering algorithm is used to automatically identify two different reactions in real-time PCR We show that the FCM clustering technique can be implemented for clustering the output results of the DNA computing readout method based on the LightCycler System.